Tin perovskite/fullerene planar layer photovoltaics: improving the efficiency and stability of lead-free devices1. Issue 21 (7th June 2015) - Marshall, Kenneth P.; Walton, Richard I.; Hatton, Ross A.
<x xml:space="preserve">Abstract</x> The preparation of CsSnI3 films at room temperature with defect densities low enough for light harvesting in photovoltaic devices is reported, along with a new strategy for improving device stability and evidence that the energetics at the perovskite/fullerene interface is a key determinant of the open-circuit voltage.